2020
DOI: 10.1021/acs.analchem.0c01926
|View full text |Cite
|
Sign up to set email alerts
|

Translation of a One-Dimensional to a Comprehensive Two-Dimensional Gas Chromatography Method with Dual-Channel Detection for Volatile Organic Compound Measurement in Forensic Applications

Abstract: After its introduction in the early 1990s, comprehensive two-dimensional gas chromatography (GC×GC) has evolved from a separation science research tool to the central component of many industries. Despite the maturity of the technique, some fields remain reluctant to its use in routine applications. In the case of forensic science, some constraints are the strict requirements enforced in forensic laboratories and the time and effort that must be invested for intralaboratory method validation. Concerns may also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The GC×GC-qMS data were used predominantly for peak identification and the GC×GC-FID data were used for quantitative information. Previous studies describe the use of this dual detection technique in combination with GC×GC and the full workflow used for processing [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GC×GC-qMS data were used predominantly for peak identification and the GC×GC-FID data were used for quantitative information. Previous studies describe the use of this dual detection technique in combination with GC×GC and the full workflow used for processing [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak integration is performed at this stage on the FID data where the acquisition rate is much higher and provides sharp and accurate peak shapes. This approach is outlined in previous publications including detector acquisition rates, number of acquisitions across a peak, and data processing workflows [ 14 , 15 ] and therefore are not described in detail here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset was kept intentionally small for this study to allow users to reproduce the analysis if desired without introducing unnecessary complexity. The instrument method was originally developed for VOC analysis in a pervious publication [5] and this method paper focuses on building upon the data processing workflow.…”
Section: Methods Detailsmentioning
confidence: 99%
“…The comprehensive GC methods can be found in Table 1. Dubois et al [29] have shown that VOCs currently being analyzed via 1D-GC for forensic purposes could be transi-tioned to a 2D-GC method without a drop in the quality of the analysis. It was found that the enhanced chromatographic separation method could be incorporated into routine examinations.…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%